(untitled) (Bangladesh Journal of Botany, 2021)
For increasing pollination and seed set, stigma exsertion has been identified as a major component in hybrid rice. By using a recombinant inbred line (RIL) population derived from an important Indica rice cross between Zhenshan97 and Minghui63, a molecular marker-based analysis of quantitative trait loci (QTL) for stigma exsertion was performed. As a result, six prominent QTL were detected for the exserted stigma rate on chromosome 6, 2, 9, 3, 5 and 1, respectively. qSER-1-1, qSER-2-1, qSER-5-1, qSER-6-1, qSER-15-1, and qSER-18-1 explained 8.1515, 4.6657, 7.2387, 4.8997, 6.925 and 6.9291% of the total phenotypic variance, respectively. In addition, for the qSER-1-1 and qSER-2-1, the ZS97B allele increased exserted stigma rate by about 4.3484 and 3.2836%, respectively; while for qSER-5-1, qSER-6-1, qSER-15-1 and qSER-18-1, the MH63 allele increased exserted stigma rate by approx. 4.1527, 3.4243, 3.9801 and 4.0025%, respectively. Bangladesh J. Bot. 50(3): 551-556, 2021 (September)